Knowledge towards type 2 diabetes among students at Universiti Teknologi Mara Arau, Perlis - Shukran, Nur Hanna Amira (Universiti Sains Malaysia, 2016)
The purpose of this cross-sectional study was to determine the knowledge towards type 2 diabetes among students at UiTM Arau, Perlis. Plan behavior theory was used as theoretical framework in this study. Self-administrated questionnaire was used and 162 subjects were recruited in this study. Patient’s Diabetes Knowledge Questionnaire, by Garcia, 2001 was been used in this study. This questionnaire comprises of 24 questions which are built from 6 domains. The domains are about general knowledge of diabetes, types of diabetes, causes, symptoms, effects and care in diabetes. The protocol of the study was being informed before participated in this study. A pilot study among 30 students that met the inclusion criteria had been done to check reliability and validity of the questionnaire. It was found that the Cronbach alpha value obtained was 0.71 and considered to be reliable. During the analysis, the score of knowledge towards type 2 diabetes was evaluated. The Pearson’s Chi Square Test was used to test on the association between score of knowledge towards type 2 diabetes with selected socio-demographic data (age, gender, levels of education, semesters of study and faculties). Among 162 respondents, it was found that only 7 (4.3%) had good knowledge towards type 2 diabetes, 63 (38.9%) had satisfactory knowledge towards type 2 diabetes and 92 (56.8%) had poor knowledge towards type 2 diabetes. There was no significant association between age, gender and levels of education with knowledge towards type 2 diabetes. However, the findings showed that semesters of study and faculties had significant association with knowledge towards type 2 diabetes. From the study, the score of knowledge towards type 2 diabetes is very low hence, showing that knowledge towards type 2 diabetes is still grossly inadequate among the general population especially the students. Massive education programmes are needed in order to equip the students with better knowledge.